Realizing Political Transpiration Peaceful Election 2024 - Fahmi*, Rizal; Sanusi, Sanusi; Rahmi, Rahmi (Universitas Syiah Kuala, 2023)
Indonesia is the country with the fourth largest population in the world, which makes every electiongenerally a major event. Since the 1998 reform, Indonesia has experienced significant progress in building an open, multiparty democratic system. Elections are the foundation of democracy that allow the people to choose their leaders and representatives. Although Indonesia has held several successful general elections, the country's electoral history has also been marked by conflict, fraud and political instability. Previous elections have faced serious challenges in terms of transparency and integrity. The 2024 general election in Indonesia is expected to be a major event that will determine the political direction and leadership of the country for the next few years. Therefore, it is important to ensure that these elections take place with high transparency, integrity and peace. Transparency in a political context involves openness and accountability in the political process, including campaigns, political financing and the implementation of elections. Transparency is key to avoiding potential manipulation and fraud in elections. Peaceful elections are the main goal in the democratic process. Protracted political conflict or violence during elections can threaten the stability of the country. Therefore, it needs to be emphasized how important it is to realize peaceful elections to maintain calm and peace in society. In the digital era, developments in information and communication technology have played a big role in general elections. In this context, it is necessary to overcome challenges related to disinformation, hoaxes and cyber attacks that can affect the integrity of elections